Financial innovations and the organisation of stock market trading - KREGEL, J.A. (PSL Quarterly Review, 2013)
Economists have never been overly interested in either the institutions comprising markets or the process of price formation in them, having instead chosen to study the possibility of the existence of “equilibrium” prices under competitive conditions. In light of the recent stock market crash, however, it is clear that the New York Stock Exchange is not a competitive market in the sense of engaging a sufficiently large number of buyers and sellers so that no individual transaction has a permanent impact on the determination of prices. This work suggests that it is the recent changes in competitive market structure which have increased the volatility of prices and made it difficult, if not impossible, for the “specialist” system of price formation to work. Proposals for change in the organisation of market trading should thus be judged relative to the prevailing imperfectly competitive conditions, rather than the ideal perfect market. JEL: G14, G15